Detection distribution of CNVs of SNX29 in three goat breeds and their associations with growth traits - Wang, Qian; Song, Xiaoyue; Bi, Yi; Zhu, Haijing; Wu, Xianfeng; Guo, Zhengang; Liu, Mei; Pan, Chuanying (Frontiers in Veterinary Science, 2023)
As a member of the SNX family, the goat sorting nexin 29 (SNX29) is initially identified as a myogenesis gene. Therefore, this study aimed to examine the polymorphism in the SNX29 gene and its association with growth traits. In this study, we used an online platform to predict the structures of the SNX29 protein and used quantitative real-time PCR to detect potential copy number variation (CNV) in Shaanbei white cashmere (SBWC) goats (n = 541), Guizhou black (GB) goats (n = 48), and Nubian (NB) goats (n = 39). The results showed that goat SNX29 protein belonged to non-secretory protein. Then, five CNVs were detected, and their association with growth traits was analyzed. In SBWC goats, CNV1, CNV3, CNV4, and CNV5 were associated with chest width and body length (P < 0.05). Among them, the CNV1 individuals with gain and loss genotypes were superior to those individuals with a median genotype, but CNV4 and CNV5 of individuals with the median genotype were superior to those with the loss and gain genotypes. In addition, individuals with the gain genotype had superior growth traits in CNV3. In brief, this study suggests that the CNV of SNX29 can be used as a molecular marker in goat breeding.